Occupational crimes in casinos: employee theft in Macau, China - Pontell, Henry N. (Crime, law and social change, 2022)
It is virtually impossible to accurately measure employee theft across the casino industry using official statistics. In this paper, we use the self-report method for measuring crime to (a) estimate the prevalence, incidence, seriousness, and versatility of occupational offending in casinos in Macau, China—the largest casino gambling location in the world; and (b) identify characteristics which correlate with that offending. One in seven employees in our sample (14%; 38 out of 281) reported engaging in at least one of six offenses (theft in the workplace, falsification of documents, computer fraud, bribe offering, bribe accepting, and white-collar exploitation) in the 12 months prior to their survey response. The great majority of active offenders specialized in crime type: 61% of the active offenders in our sample (23 out of 38) committed just one of the six occupational crimes. Criminal "specialization" notwithstanding, offenders committed their crimes relatively frequently; occupational crimes were particularly costly to casinos in the long run; and these offenses varied in their severity and extent depending on crime type. Demographic characteristics of casino employees—in particular, male gender, occupational position, work schedule, and work-related experience—were associated with whether an employee engaged in workplace crime. Regarding psychological and lifestyle characteristics of employees, only financial pressure and gambling behavior were significantly related to occupational offending. Given that casinos are subject to high levels of surveillance relative to other places of employment, criminal motivation, and not just opportunity, could matter in terms of crimes committed by workers in the gaming industry.